Studi Kandungan Residu Antibiotik Kloramfenikol pada Produk Pangan Olahan Madu, Udang, dan Ikan di Sulawesi dan Maluku - Ebtasari, Ma'rifah; Aini , Alifah Nur (Eruditio : Indonesia Journal of Food and Drug Safety, 2024)
Antibiotic residues in food products can cause significant public health problems. Using antibiotics in livestock farming can potentially cause antibiotic residues in animal-based foods. We conducted this study to determine the results of chloramphenicol residue testing in processed honey, shrimp, and fish food products in the Sulawesi and Maluku regions. This study can determine the distribution of test results based on business type. This study is expected to produce recommendations to stakeholders to minimize the use of chloramphenicol, which is not covered by the provisions. The research samples came from processed honey, shrimp, and fish food products distributed in the Central Sulawesi, Ambon, Sofifi, Mamuju, Morotai, and Tanimbar regions in 2021-2022. Testing was carried out at the laboratory of the Indonesian Food and Drug Authority Regional Office in Palu according to the analysis method of PPPOMN 071/PA/17 concerning the Determination of Chloramphenicol Residue Levels in Shrimp by ELISA and MA PPPOMN 11/PA/09 concerning the Determination of Chloramphenicol Residue Levels in Honey by ELISA. Based on the test results, processed honey, shrimp, and fish food products were found to contain chloramphenicol residues. Of the total 92 samples tested, there were 15 honey products, four processed shrimp food products, and seven processed fish food products that did not meet the requirements (TMS). Chloramphenicol residue levels ranged from 0.01 to 0.09 ppb. The number of TMS samples in honey and fish food products with PIRT distribution permits was more significant in percentage when compared to products with MD/ML distribution permits. The rate of TMS in honey and processed fish food products with PIRT distribution permits was 53% and 21%, respectively. Further research on the source of chloramphenicol residues and the origin of honey, shrimp, and fish-producing areas needs to be conducted by relevant institutions or academics. In addition, it is necessary to conduct socialization and education among the public regarding the use of chloramphenicol antibiotics according to the provisions for both the treatment of diseases and livestock practices to minimize the presence of chloramphenicol residues in processed food products.